Social Media Usage and Peer Pressure as Predictors of Substance Abuse among In-School Adolescents in Kwara State, Nigeria - Alwajud-Adewusi, Mariam Bukola; Oduola, Olayemi Zainab; Ifabiyi, Bolanle (Jurnal Kajian Bimbingan dan Konseling, 2025)
Substance abuse among youngsters in Nigeria is worrisome. Its consequences include acute, chronic diseases as well as social and psychological ailments. Immediate intervention is essentially paramount to prevent the future of the younger generation. Thus, this study investigated social media usage and peer pressure as predictors of substance abuse among in-school adolescents in Kwara state, Nigeria. The study was a survey research. The population of this study comprised all in-school adolescents in Secondary Schools in Kwara State which estimated at 247,845. The sample size of 403 participated in the study. An instrument entitled “Social Media Usage, Peer Pressure and Substance Abuse” was used to collect data. The validity and reliability of the instrument were established. Data was analysed using Mean, Multiple Regression Analysis and Pearson’s Product Moment Correlation (PPMC) at 0.05 alpha level. The findings of the study revealed that in-school adolescents engaged in high level of social media usage. It showed that in-school adolescents experienced high level of peer pressure. Findings further revealed that in-school adolescents’ level of substance abuse is low. It showed that social media usage and peer pressure significantly predicted substance abuse among in-school adolescents in secondary schools in Kwara State, Nigeria. Based on the findings of this study, it was recommended that school managements should develop and implement educational and mentoring support programs. These initiatives can help create awareness on social media usage and provide students with the assertiveness skills to resist negative peer pressure.